A cost benefit analysis of elimination of kala-azar in Indian subcontinent:an example of Nepal - Shiva Raj Adhikari , Siripen Supakankunti (Journal of Vector Borne Diseases, 2010)
Background & objectives: Visceral leishmaniasis, locally known as kala-azar (KA) has beenconsidered as a major public health problem in Bangladesh, India and Nepal that affects 100,000people per year with 147 million people at risk. Elimination of infectious disease is an ultimategoal of the public health system, therefore, the efforts have recently gained momentum from variousorganizations and governments to expand KA interventions in the endemic countries. The paperaims to estimate discounted net benefits and internal rate of return (IRR) to evaluate the economicfeasibility for elimination of KA by utilizing available secondary information.Methods: Cross-sectional data were collected from different sources to estimate societal costs ofand benefits from KA interventions with a 13-year project period. Total costs are estimated basedon the unit cost of inputs used for interventions. The benefits are derived from productivity changeand resources saved due to reduction of KA incidence. Net benefits and IRRs are estimated basedon standard procedures used in the field of economics, subsequently the sensitivity analysis isconducted.Results: A total discounted net benefit of KA intervention is Nepalese Rupees (NRs) 65,287 millionwith 35% IRR. The result suggests that for every rupee invested in KA intervention at present willyield NRs 71 in future. The regional benefits from the interventions will be greater than the sum ofbenefits gained by the individual country due to its nature of public goods.Conclusion: Elimination of KA is a good investment opportunity for the Government andinternational partners involved in the health sector.